Świadomość nauczycieli dotycząca uczniów o podwójnej wyjątkowości i stosowane wobec nich podejścia edukacyjne: analiza porównawcza Turcji, Polski, Czech, Włoch i Bułgarii - Şentürk, Şener; Gierczyk, Marcin; Dobosz, Dagmara; Emecan, Banu İlhan and Boneva, Daniela and Gallo, Florian and Kefeli, İdil and Krejčová, Lenka and Moroń, Marcin and Vural, Murat and i in. (Studia Edukacyjne, 2025)
The study aimed to investigate the teachers’ awareness regarding twice-exceptional students. We investigated two domains of such awareness, namely, awareness of special needs, learning difficulties, and socio-emotional problems faced by the twice-exceptional student and self-efficacy in the area of instructional strategies, legal regulations, and knowledge about how to proceed with the twice-excep- tional student. Our research has shown that teachers have a relatively high level of awareness of the specific needs of students with special educational needs, regardless of the cultural context. Teachers from Turkey, Poland and Bulgaria showed a higher awareness compared to their colleagues from the Czech Republic and Italy.